Special Focus Introduction: Centering Black Cultural Production in Translation - Corine Tachtiris; Priscilla Layne (Studies in 20th & 21st Century Literature, 2023)
Special Focus Introduction: Centering Black Cultural Production in Translation
Keywords: translation; race; Blackness; diaspora